The embodied imagination in antebellum American art and culture - Holochwost, Catherine, author.
1 online resource.
Keywords: "This book reveals a new history of the imagination told through its engagement with the body. American audiences avidly consumed a transatlantic visual culture picturing a preindustrial-and largely imaginary- European past. By examining both the artistic production and critical and popular reception of these works, the book analyzes their similarities with other forms of mass culture, including gift books, theatrical performances and spectacles such as blackface minstrelsy, Romantic ballet, and burlesque opera. The book will be of interest to scholars of art history, literary and cultural history, critical race studies, performance studies, and media studies"--